2020
DOI: 10.1007/s10072-020-04957-7
|View full text |Cite
|
Sign up to set email alerts
|

An overview on amyotrophic lateral sclerosis and cadmium

Abstract: The present review represents an update about the knowledge of the possible role of Cadmium (Cd) in amyotrophic lateral sclerosis (ALS) initiation and its progression. ALS is a neurodegenerative disease that occurs in adulthood; its etiology is unknown and leads to death within a few years from its appearance. Among the various possible causes that can favor the development of the disease, heavy metals cannot be excluded. Cadmium is a heavy metal that does not play a biological role, but its neurotoxicity is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In an animal model, similarly, chronic exposure to PM resulted in a dose-dependent increase in pure cortical neuronal loss and selective neuronal loss especially of the motor cortex, primary somatosensory cortex, and piriform cortex [60]. In addition, traffic-related pollution may contain elements characterized by neurotoxic effects, especially heavy metals such as lead, cadmium, mercury, and selenium already associated with ALS risk [61][62][63][64][65][66]. A neuroimaging study showed that long-term exposure to high ambient air pollution may lead to cortical thinning and reduced subcortical volume in adults [67].…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, similarly, chronic exposure to PM resulted in a dose-dependent increase in pure cortical neuronal loss and selective neuronal loss especially of the motor cortex, primary somatosensory cortex, and piriform cortex [60]. In addition, traffic-related pollution may contain elements characterized by neurotoxic effects, especially heavy metals such as lead, cadmium, mercury, and selenium already associated with ALS risk [61][62][63][64][65][66]. A neuroimaging study showed that long-term exposure to high ambient air pollution may lead to cortical thinning and reduced subcortical volume in adults [67].…”
Section: Discussionmentioning
confidence: 99%
“…Rare Earth Elements:Yttrium (Y), Lanthanum (La), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Terbium (Tb), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Ytterbium (Yb), Lutetium (Lu) [205,282,[284][285][286][287] Coexistence of multiple metal NPs alter the original toxicity of individual NP [285,288] Detection of metalloid, Si [290], which may be of relevance in the veterans from the Gulf Wars where desert dust (e.g. SiO 2 ) and particulate matter are prevalent [291] Si NPs 7 + nm evoke oxidative stress and mitochondrial dysfunction [292,293] Within neurons, microglia, oligodendrocytes, astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For these methodological and statistical reasons, potential sub-phenotypes or dynamics in the clinical course were not considered in our study. The identification of the potential toxic agent(s) [42][43][44][45] in terms of plausibility and mechanism of action will be the object of future studies.…”
Section: Discussionmentioning
confidence: 99%